Coherent splitting of two-dimensional Bose gases in magnetic potentials - Barker, AJ; Sunami, S; Garrick, D; Beregi, A; Luksch, K; Bentine, E; Foot, CJ (IOP Publishing, 2020)
Investigating out-of-equilibrium dynamics with two-dimensional (2D) systems is of widespread theoretical interest, as these systems are strongly influenced by fluctuations and there exists a superfluid phase transition at a finite temperature. In this work, we realise matter-wave interference for degenerate Bose gases, including the first demonstration of coherent splitting of 2D Bose gases using magnetic trapping potentials. We improve the fringe contrast by imaging only a thin slice of the expanded atom clouds, which will be necessary for subsequent studies on the relaxation of the gas following a quantum quench.